(untitled) (Vallis Aurea, 2017)
The aim of the paper was to analyze the structure of the effect of the observed elements of the promotional mix on the selection of sports products in Slavonski Brod. The analysis was conducted on a sample of 385 entities. According to the results of the research, no element was considered as dominant in the structure of the influence of the elements of the promotional mix in the choice of practicing a sports product. Propaganda was slightly highlighted as the most important element of the promotional mix. It should also be emphasized that in selecting a sports product, the promotion factor, as one of the 4 marketing mix factors, achieves relatively small, only 14.5% of the frequency. The results also show that the sports product in Slavonski Brod is price-sensitive and contentually acceptable, that sporting is extremely important, but the problems of resource allocation as time are quite questionable, which is surprising. It can be said that both the product and the price are dominant as a choice which is expected from the aspect of sports consumers. This is a direct message to the sports program providers what needs to be directed on. Indirectly, however, it can be said that the promotion could and should be significantly more qualitative and quantitatively represented. First and foremost, this refers to a set of activities that enable consumers to inform about the product on market or to promote their sports products, which is probably missing out.